2005
DOI: 10.2106/jbjs.d.01751
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Supracondylar-Intercondylar Distal Femoral Fractures and Coronal Plane Fractures

Abstract: Coronal plane fractures frequently occurred in association with high-energy supracondylar-intercondylar distal femoral fractures; in the present study, the prevalence of associated coronal plane fractures was 38%. The lateral condyle was involved more frequently than the medial condyle was. Coronal plane fractures of both condyles were observed commonly, and the majority of coronal plane fractures were associated with open wounds. Since the surgical tactic for the treatment of a supracondylar-intercondylar dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
132
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 21 publications
2
132
1
8
Order By: Relevance
“…3,4 A few cases of Hoffa fractures associated with supracondylar-intercondylar femoral fractures have also been described in the literature. 1,2,8 Our patient had an eminentia fracture with PCL injury in addition to the rarely seen medial Hoffa fracture, which further complicated the damage. In any such unusual pattern of injuries, the diagnosis of additional bone and soft-tissue trauma is important in planning treatment and achieving functionally satisfying results.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…3,4 A few cases of Hoffa fractures associated with supracondylar-intercondylar femoral fractures have also been described in the literature. 1,2,8 Our patient had an eminentia fracture with PCL injury in addition to the rarely seen medial Hoffa fracture, which further complicated the damage. In any such unusual pattern of injuries, the diagnosis of additional bone and soft-tissue trauma is important in planning treatment and achieving functionally satisfying results.…”
Section: Discussionmentioning
confidence: 89%
“…[1][2][3][4][5][6][7][8] Although usually only one condyle is involved, bilateral and unilateral bicondylar Hoffa fractures have been reported. 3,4 A few cases of Hoffa fractures associated with supracondylar-intercondylar femoral fractures have also been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nork et al [1] reported an association of around 38% with supracondylar/intercondylar distal femoral fractures, and among them, 85% of the coronal fractures involved the lateral femoral condyle. Bony avulsion of PCL from the tibia in addition to type C distal femoral fractures with a HoVa fracture of the lateral condyle has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Vengono classificate secondo la classificazione OTA/AO, che risulta utile per stabilire il trattamento e la prognosi. Tali fratture seguono linee di debolezza dovute alla conformazione stessa del terzo distale di femore: la zona di passaggio da diafisi a metafisi, la gola intercondilica sul piano sagittale, il solco trocleo condiloideo, talché spesso sono pluriframmentate; inoltre, l'inserzione a tale livello di componenti muscolari (quadricipite, gastrocnemio, adduttori) rende estremamente difficoltosa la riduzione dei vari frammenti di frattura nei piani ortogonali [2,3]. Il trattamento conservativo è raro e viene riservato a pazienti allettati o con mobilità ridotta in fratture composte o minimamente scomposte [4].…”
Section: Introduzioneunclassified